FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2008-2010) - S. Kristian, 08.3503.0708; Lisiantara, Greg. Anggana (Students Journal of Accounting and Banking, 2013)
One of the qualitative characteristics of financial reporting is relevant, the manifestations can be seen from ketepatwaktuan reporting. Ketepatwaktuan can be traced from the audit delay, ie the period between the closing date until the date of the auditors report. This study aims to test empirically the effect of firm size, profitability, solvency and quality auditor to audit delays in manufacturing companies listed on the Indonesia Stock Exchange. Based on the selection criteria in this study found 41 companies, which generate 123 a data pooling. Analytical methods used to analyze the influence of company size, profitability, solvency and quality auditor to audit delay is multiple linear regression analysis. The results of this study can be concluded that: (1) firm size has a positive effect on audit delay, meaning the higher the size of the company, the audit firms delay longer. (2) does not affect the profitability of audit delay. (3) Solvency no effect on audit delay. (4) The quality auditor negative effect on audit delay, meaning the better the quality of auditors, it will have a shorter delay time audt.Keywords: firm size, profitability, solvency, quality auditors and audit delay